Cidades sustentáveis: conteúdos e limites do Estado Ambiental na perspectiva de uma teoria estruturante - Coutinho, Ricardo Silva (2016)
This research is committed to a reflection on the performance of the Environmental State in view of the Structuring Theory of Law (Friedrich Müller), by observing the construction of protection norms for sustainable cities with a method that analyzes the structure of state decisions. Engaged in formulating integration criteria for empirical data in decision-making processes, such methodology enables practical implementation of norms and protective measures for urban spaces by developing solutions with higher standards of reasoning and justification, and establishing a better control of the contents and limits of environmental protection. From this viewpoint, sustainable cities are conceived as a domain that provides for economic, political and social development without compromising natural resources – one that creates ways to ensure environmental balance and access to fundamental rights, including cultural and natural assets, in order to guarantee quality of life for its inhabitants. This research has two parts. In the first one, we show the constitutional foundations of the Environmental State in Brazil, i.e., the constitutional basis of a form of state that tends to prioritize the protection of the environment as an overarching goal in all of its decision-making processes. In the second part, we advance the construction of the contents and limits of the protection of cities, by employing a methodology that rationalizes the construction of norms of environmental protection with the notions of "norm program" and "norm scope", and by identifying endogenous and exogenous aspects regarding the legal system – all with the aim of improving the practical implementation of the law in the protection of the urban environment by the Environmental State. These measures therefore contribute to greater correctness and effectiveness of state actions, in view of the constitutional objective of creating more sustainable cities